Synergistic Pathological Effect of Mycoplasma gallisepticum with other Infectious Organisms in Layer Chickens - Sivaseelan , Soundarapandian; Malmarugan , Shanmugasamy; Balasubramaniam, Perumal Balachandran Gurusamipalayam Amirthalingam (Brazilian Journal of Veterinary Pathology, 2013)
Synergistic pathological effect of Mycoplasma gallisepticum with other infectious organisms in layer chickens was evaluated in 70 commercial layer chicken farms. Newcastle disease virus and infectious bronchitis virus were confirmed by haemagglutination inhibition test (HI), and Escherichia coli, Pasteurella multocida, Haemophilus paragallinarum and Ornithobacterium rhinotracheale were confirmed by their growth characteristics on agar media and Gram’s staining. PCR technique was used for the confirmation of Mycoplasma gallisepticum. The mortality rates observed in the occurrence of individual diseases were synergistically increased when they combined with chronic respiratory disease (CRD), which was clearly supported by the gross and histopathological alterations.